Assessing the effectiveness of cover crops on ecosystem services: a review of the benefits, challenges, and trade-offs - Maryam Yousefi; Anne Dray; Jaboury Ghazoul (International Journal of Agricultural Sustainability)
While it is crucial to consider the ecological trade-offs of cover crop effects to promote sustainable agricultural production, there has been limited analysis of the combined effects of cover crops on various ecosystem services. For this purpose, we synthesized 43 meta-analysis and review studies comparing cover crops to monocropping in order to investigate benefits, challenges, and trade-offs among ecosystem services under cover crop implementation. We summarized the current state of knowledge of cover crops effectiveness across 11 ecosystem services in three categories (regulating, provisioning and supporting). We identified the factors influencing the relative benefits and risks of integrating cover crops into crop production systems. These factors include farm practices, planting and termination season, species of cover and main crop, climatic zone and soil properties, cover crop biomass, and residue management. Our findings highlight that compared to monocropping, in general, cover cropping enhances soil biodiversity and nutrient cycling, prevents runoff and Nitrogen leaching, improves soil physical properties and carbon sequestration over the long term, and suppresses pests and weeds. However, trade-offs comprise inconsistencies in primary crop yields and soil water provision. Overall, our result highlighted that a multifunctional cover crop implementation provides substantially more regulating and supporting than other ecosystem services.